PENGARUH ZAT ADITIF TERHADAP KUAT TEKAN BETON K-225 MENGGUNAKAN BATU BASALT SCORIA - Cahya Sujatmiko (TEKNIKA SAINS, 2018)
Indonesia is a developing country that is doing a lot of development in all areas such as: the construction of buildings, bridges, dams, canals, and others. Various studies and experiments in the concrete field are carried out as an effort to improve the quality of concrete, material technology and implementation techniques obtained from the results of research and experiments intended to answer the increasingly high demands on the use of concrete and overcome the obstacles that often occur in the implementation work at outdoor. The use of added materials (Admixture) can help solve these problems. The purpose of this study was to determine the extent of the influence of additives on the compressive strength of k-225 concrete using basalt scoria stone. The making of k-225 concrete used cuboid sized molds (15cm x 15cm x 15c) in research into the manufacture of concrete to produce high quality concrete. The research method used was an experimental method conducted at the laboratory of PT. Gig Polah Raya Jl. Lintas Sumatera KM 22 Sukabandung South Lampung, namely by carrying out or physically experimenting on concrete tests, which used additives, as many as 24 test objects, namely 6 without additives and 6 additives 0.45%, and 0.55% and 0.63% and normal compressive strength k-225. The aim is to know the average compressive strength between normal concrete and concrete using a mixture of additives as a reference.